2007
DOI: 10.1097/01.ta.0000243203.38466.e0
|View full text |Cite
|
Sign up to set email alerts
|

Early Unreamed Intramedullary Nailing of Femoral Fractures is Safe in Patients With Severe Thoracic Trauma

Abstract: Early unreamed IMN of femoral fractures in multiply injured patients with severe thoracic trauma is a safe procedure and seems to be justified to achieve early definitive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…The influence of associated injury on the timing of definitive management of mechanically unstable fractures is debated. [12][13][14][15][16][17][18][19][20][21][22][23][24] The practice of "early total care," including early definitive fracture management, has been criticized because additional hemorrhage from surgery may incite a deleterious systemic inflammatory response. 17,19,25,26 The alternative extreme of "damage control orthopedics" (DCO) has been recently proposed as a means of providing provisional stability of major skeletal injury, generally through external fixation.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of associated injury on the timing of definitive management of mechanically unstable fractures is debated. [12][13][14][15][16][17][18][19][20][21][22][23][24] The practice of "early total care," including early definitive fracture management, has been criticized because additional hemorrhage from surgery may incite a deleterious systemic inflammatory response. 17,19,25,26 The alternative extreme of "damage control orthopedics" (DCO) has been recently proposed as a means of providing provisional stability of major skeletal injury, generally through external fixation.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of sepsis related to pulmonary dysfunction can likewise be lessened in these patients. Early fracture fixation had a positive effect on pulmonary and cardiovascular parameters (24). In our series, patients who came to the emergency department for acute femoral shaft fracture received surgery as early as possible (average 2 days, range 1-4 days) and were mobilized early in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Intramedullary nailing can provide for early mobilization in patients with multiple trauma, thereby reducing mortality and morbidity (24,25). Retrospective studies of patients with multiple injuries emphasize that fracture fixation performed within the first 24 hours is associated with lower mortality (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that combined fracture and soft tissue injury caused higher levels of systemic inflammatory mediators (IL-6 and IL-10) than either fracture of soft tissue injury alone. The literature on SIRS and orthopedic trauma is extensive (Hardwood et al, 2005;Seibel et al, 1985;Scalea 2000;Olson, 2004;Schroeder et al, 2009;Sears et al, 2009;Weninger et al, 2007) with the femoral fracture being the primary model since it is a long bone fracture and is often most related with systemic and pulmonary collapse secondary to injury and surgery. Concern about the timing of definitive intramedullary fixation, which includes intramedullary reaming and further release of marrow contents and inflammatory mediators, is an ongoing debate in the orthopedic trauma community.…”
Section: Systemic Responsementioning
confidence: 99%